Successful pregnancy outcome in an untreated case of concomitant transverse complete vaginal septum with unicornuate uterus - Kumar, Naina (J Hum Reprod Sci, 2014)
Transverse vaginal septum is a result of faulty canalization of embryonic vagina. Septum may be complete but usually has laterally placed tiny hole giving an impression of vaginal vault without cervix. We described a case of untreated transverse vaginal septum with small central aperture diagnosed during labor and unicornuate uterus diagnosed intraoperatively, with successful pregnancy outcome.